Studi Korelasional antara Komunikasi Guru-Orang Tua, Lingkungan Sekolah, dan Karakter Peserta Didik - Nurasiah, Siti; Al-Hamdani, M.Djaswidi (Tsamratul Fikri | Jurnal Studi Islam, 2016)
This research article found three conclusions as follows: (1) the test results of the relationship between teacher-parent communication with the character of students in the study site shown to correlate very high positive figures indicate a correlation coefficient of 0.875. Therefore, the relationship between teacher-parent communication with learners characters proved to be very strong, so the better the teacher-parent communication, then it will be better the character of the students. (2) the test results of the relationship between the school environment with the character shown to correlate positively learners very high figures indicate the correlation coefficient of 0.709. Thus, the relationship between the school environment with the character of the students proved to be very strong, means the better the school environment, then it will be better the character of the students. (3) the test results of the relationship between teacher-parent communication and school environment together with the character of students proved their extremely high correlation figures indicate the correlation coefficient of 0.877. The third hypothesis in the research are accepted. tween the test results Variable X1 and X2 together with a variable Y, where the figures obtained multiple correlation coefficient of 0.972. Therefore, understanding parents about education and parental involvement in the education practice a very important role in improving the learning outcomes of students. ion coefficient of 0.752 (included in the category of very strong).